MANAJEMEN RISIKO TERHADAP PELAKSANAAN PROYEK KONSTRUKSI HOTEL DI KAWASAN SARBAGITA - I Nyoman Martha Jaya; Dewa Ketut Sudarsana; Gusti Ayu Kade Intan Wiratni (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2019)
RISK MANAGEMENT DURING IMPLEMENTATION OF HOTEL CONSTRUCTION PROJECT AT SARBAGITA AREA ABSTRACT Construction project is an unique project and constrained by cost, quality and time. During construction project implementation, problems are frequently occur that affect toward cost, quality and time. Therefore according to such matter, it is considerably necessary to conduct research concerning risk management. Risk management include risk identification, risk analysis, risk acceptance distribution, risk mitigation and risk ownership. This research was conducted through interview with expert parties in hotel construction project implementation at Sarbagita (Denpasar, Badung, Gianyar, and Tabanan) region. This research aimed to identify and determine risk acceptance level, determine dominant risk, conduct mitigation action and risk ownership allocation. Total risks identified in this research were 37 risks that consist of 19 risks according to literature and 18 new finding risks. Dominant risk in this research were 28 risks, classified into 19 undesirable risks and 9 unacceptable risks. Both risks frequently occur in upper structure work. The most frequent risk sources occur in undesirable and unacceptable risks were technical risk. Technical risk in unacceptable risk were difference between picture and actual field, inaccurate scheduling, picture problems from planner and material specification discontinuation. Technical risk in undesirable risk were mainly tools mobilization delay, working hours limitation, quality and specification inconsistency and material discontinuation. Mitigation action mostly performed in technical risk were such as communication escalation between involved parties and organization structure improvement and project administration. Largest risk ownership allocation were in contractor side. These were due to contractor as the most responsible party in construction project implementation.